1997
DOI: 10.1183/09031936.97.10071530
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia: the annual cost to the National Health Service in the UK

Abstract: The aim of this study was to estimate the direct annual healthcare costs to the UK National Health Service (NHS) of managing community-acquired pneumonia.Using a prevalence-based burden of illness approach, health service resource use and corresponding costs attributable to the management of community-acquired pneumonia during 1992/1993 in the UK were obtained from published sources and commercial databases, and supplemented by a telephone survey of general practitioners, finance directors, community nurses, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
2
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 12 publications
3
140
2
14
Order By: Relevance
“…Treatment failure was also associated with more complications and a longer stay in hospital 28 which contributes to an increase in expenses as the cost per day of hospitalisation represents the highest health care cost for CAP. [29][30][31] This study has identified, at the time of hospital admission, patients who are especially prone to early and late treatment failure with an 11-fold higher mortality. Patients with liver disease, leucopenia, multilobar CAP, initial severity, and cavitation or pleural effusion on chest radiography have a higher risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure was also associated with more complications and a longer stay in hospital 28 which contributes to an increase in expenses as the cost per day of hospitalisation represents the highest health care cost for CAP. [29][30][31] This study has identified, at the time of hospital admission, patients who are especially prone to early and late treatment failure with an 11-fold higher mortality. Patients with liver disease, leucopenia, multilobar CAP, initial severity, and cavitation or pleural effusion on chest radiography have a higher risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…This accentuates the importance of prompt, accurate diagnosis and severity of illness which approaches to decisions regarding the extremity of management. [19,20] 200 patients with CAP were enrolled in this study. The current study asserts that B/A ratio with 97.1 % sensitivity and 100 % specificity with AUC of 0.999 is a better marker for the deciding severity, need of ICU and development of any complications during the course of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Los costos del cuidado de esta enfermedad han sido crecientes, concentrándose en los pacientes hospitalizados y admitidos a unidades de cuidado crítico por NAC grave 4,15 . Considerando que estamos en presencia de una patología infecciosa prevenible, cuya historia natural es conocida y que determina un quiebre en la caliEpidemiología de la neumonía del adulto adquirida en la comunidad -G. Valdivia C. …”
Section: (Figura 3) [Ii]unclassified
“…En cuanto a los cuidados mé-dicos otorgados a la población, la NAC ofrece la oportunidad de evaluar críticamente la gestión clínica, concordancia en el uso de arsenales terapéuticos atingentes con la realidad epidemiológica y la adecuada categorización de la gravedad del cuadro de neumonía utilizando los criterios disponibles para ello 4,8,9 . El manejo de esta enfermedad infecciosa conlleva el gasto de importantes recursos económicos susceptibles de ser reducidos, considerando que se trata de una patología prevenible 15 . Esto implica la generación, difusión y adherencia a protocolos y guías clínicas consensuadas y la provisión de atención en cantidad y oportunidad adecuadas.…”
Section: Conclusionesunclassified